(untitled) (Research, Society and Development, 2020)
The teaching of genetics faces constant problems with the methods employed by biology teachers in basic education. In addition, it is noted that this is one of the difficult to understand subjects, missing connecting concepts and subjects for students at different educational levels. Thus, the objective was to build and propose the use of conceptual maps applicable to the teaching of genetics. From studies conducted in specialized bibliographies, two maps of concepts related to genetics were built in order to be further tested as facilitating instruments in the teaching-learning process. The first concept map was built with fundamental concepts about genetic material, DNA and RNA, with genomic information associated with prokaryotes, eukaryotes and viruses. In relation to the second map, it was built on the basis of information about the pathways by which DNA molecules express the information they conduct within the cell, or will transmit that information to another cell or another organism. Both maps were developed with fluid and comprehensive reading, which can be used as facilitating tools for teaching and learning of traditional and current genetics content.